Peran Majelis Taklim Al-Hidayah dalam Pendidikan Islam dan Gerakan Sosial Keagamaan di Propinsi Lampung - Rumadani Sagala (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2019)
The era of globalization of life has been integrated with the cyber world with the need to foster religious life, one of which is conducting non-formal education such as the Majlis ta'lim which has been investigated lately. Lampung province for Islamic education and socio-religious movements. Specifically, this research plan will raise the role, role, strategy of institutional development by taking studies at the Majelis Taklim Al-Hidayah Bandar Lampung, East Lampung, Central Lampung, and Pesawaran. The method of this research is a qualitative approach by providing a qualitative description of the role of the Al-Hidayah clerics in Islamic education and socio-religious movements. The results of this study that the existence of the Lampung province's Al-Hidayah study during the research process was carried out since mid-2018, demonstrating its role, duties and functions as non-formal educational institutions that engaged in women's groups in order to strengthen maternal capacity and knowledge especially in Islamic education religious social movements.